GRAPHIC USER INTERFACE ON VIRTUAL REALITY TOUR SCENE OF SIMIGAPI - Agatha Maisie Tjandra (Universitas Multimedia Nusantara, 2018)
(Simulasi Mitigasi Gunung Berapi- mitigation simulator volcanic eruption) is an application of serious game with story line by using virtual reality using head mounted display. There are three parts of SIMIGAPI based on the process of mitigation. The main focus of this paper is on the evacuation parts. In this part, user are given a mission to escape from volcanic ashes by walking through the virtual world and passing the pin points. Briefing are given by using text, and graphic elements using 3D graphic user interface. On the other hand, bad user interface may decrease the immersive purposes and easily children as user can be bored. This automatically can affect failed the process transferring information evacuation mitigation to user. This paper aim to explain about creating 3D user interface and observing user experience for education purposes on evacuation part of SIMIGAPI. This project use production method and quantitative questionnaire test to know user perspective about SIMIGAPI information by using GUI.